An ESP Textbook Analysis: The Case of English for Civil Engineering - Zulis Astuti (Jetlal, 2022)
In this study, the authors evaluate the ESP textbooks that were institutionally prepared for students of Civil Engineering and the Faculty of Engineering, University of Muhammadiyah Malang. The analysis for evaluating textbooks in this study used a qualitative descriptive method based on the Cunningsworth and Miekley checklist. The rating scale points evaluated include very good, good, moderate, and poor. The results showed that almost all categories were marked enough to meet the evaluation textbook criteria proposed by Cunningsworth and Mickley. This is because of textbook only focuses on vocabulary enrichment. Several recommendations for improvement and revision of textbooks are given at the end of this research, especially those related to the material.